The rough endoplasmatic reticulum is a central nucleation site of siRNA‐mediated RNA silencing. (19th March 2013) - Stalder, Lukas; Heusermann, Wolf; Sokol, Lena; Trojer, Dominic; Wirz, Joel; Hean, Justin; Fritzsche, Anja; Aeschimann, Florian; Pfanzagl, Vera; Basselet, Pascal; Weiler, Jan; Hintersteiner, Martin; et al.
<x xml:space="preserve">Abstract</x> Despite progress in mechanistic understanding of the RNA interference (RNAi) pathways, the subcellular sites of RNA silencing remain under debate. Here we show that loading of lipid‐transfected siRNAs and endogenous microRNAs (miRNA) into RISC (RNA‐induced silencing complexes), encounter of the target mRNA, and Ago2‐mediated mRNA slicing in mammalian cells are nucleated at the rough endoplasmic reticulum (rER). Although the major RNAi pathway proteins are found in most subcellular compartments, the miRNA‐ and siRNA‐loaded Ago2 populations co‐sediment almost exclusively with the rER membranes, together with the RISC loading complex (RLC) factors Dicer, TAR RNA binding protein (TRBP) and protein activator of the interferon‐induced protein kinase (PACT). Fractionation and membrane co‐immune precipitations further confirm that siRNA‐loaded Ago2 physically associates with the cytosolic side of the rER membrane. Additionally, RLC‐associated double‐stranded siRNA, diagnostic of RISC loading, and RISC‐mediated mRNA cleavage products exclusively co‐sediment with rER. Finally, we identify TRBP and PACT as key factors anchoring RISC to ER membranes in an RNA‐independent manner. Together, our findings demonstrate that the outer rER membrane is a central nucleation site of siRNA‐mediated RNA silencing.